Impact of chronic obstructive pulmonary disease and dyspnoea on clinical outcomes in ticagrelor treated patients undergoing percutaneous coronary intervention in the randomized GLOBAL LEADERS trial. Issue 4 (9th December 2019) - Tomaniak, Mariusz; Chichareon, Ply; Takahashi, Kuniaki; Kogame, Norihiro; Modolo, Rodrigo; Chang, Chun Chin; Spitzer, Ernest; Neumann, Franz-Josef; Plante, Sylvain; Hernández Antolin, Rosana; Jambrik, Zoltan; Gelev, Valeri; et al.
Abstract: Aims: To evaluate long-term safety and efficacy of ticagrelor monotherapy in patients undergoing percutaneous coronary interventions (PCIs) in relation to chronic obstructive pulmonary disease (COPD) at baseline and the occurrence of dyspnoea reported as adverse event (AE) that may lead to treatment non-adherence. Methods and results: This is a non-prespecified, post hoc analysis of the randomized GLOBAL LEADERS trial ( n = 15 991), comparing the experimental strategy of 23-month ticagrelor monotherapy following 1-month dual antiplatelet therapy (DAPT) after PCI with the reference strategy of 12-month DAPT followed by 12-month aspirin monotherapy. Impact of COPD and dyspnoea AE (as a time-dependent covariate) on clinical outcomes was evaluated up to 2 years. The primary endpoint was a 2-year all-cause mortality or non-fatal, centrally adjudicated, new Q-wave myocardial infarction. The presence of COPD ( n = 832) was the strongest clinical predictor of 2-year all-cause mortality after PCI [hazard ratio (HR) 2.84; 95% confidence interval (CI) 2.21–3.66; P adjusted = 0.001] in this cohort ( n = 15 991). No differential treatment effects on 2-year clinical outcomes were found in patients with and without COPD (primary endpoint: HR 0.88; 95% CI 0.58–1.35; P = 0.562; P int = 0.952). Overall, at 2 years dyspnoea was reported as an AE in 2101 patients, more frequently among COPD patients, irrespective of treatment allocation (27.2% in experimental arm vs. 14.5% in reference arm, P = 0.001). Its occurrence was not associated with a higher rate of the primary endpoint ( P adjusted = 0.640) in the experimental vs. the reference arm. Conclusion: In this exploratory analysis, COPD negatively impacted long-term prognosis after PCI. Despite higher incidence of dyspnoea in the experimental arm, in particular among COPD patients, the safety of the experimental treatment strategy appeared not to be affected. Clinical trial registration unique identifier: NCT01813435.